An improved method for measuring catalase activity in biological samples - Hadwan, Mahmoud Hussein; Hussein, Marwah Jaber; Mohammed, Rawa M; Hadwan, Asad M; Saad Al-Kawaz, Hawraa; Al-Obaidy, Saba S M; Al Talebi, Zainab Abbas (Biology methods and protocols, 2024)
Catalase (CAT) is an important enzyme that protects biomolecules against oxidative damage by breaking down hydrogen peroxide (H2O2) into water and oxygen. CAT is present in all aerobic microbes, animals, and plants. It is, however, absent from normal human urine but can be detected in pathological urine. CAT testing can thus help to detect such urine. This study presents a novel spectrophotometric method for determining CAT activity characterized by its simplicity, sensitivity, specificity, and rapidity. The method involves incubating enzyme-containing samples with a carefully chosen concentration of H2O2 for a specified incubation period. Subsequently, a solution containing ferrous ammonium sulfate (FAS) and sulfosalicylic acid (SSA) is added to terminate the enzyme activity. A distinctive maroon-colored ferrisulfosalicylate complex is formed. The formation of this complex is a direct result of the reaction between FAS and any residual peroxide present. This leads to the generation of ferric ions when coordinated with SSA. The complex has a maximum absorbance of 490 nm. This advanced method eliminates the need for concentrated acids to stop CAT activity, making it safer and easier to handle. A comparative analysis against the standard ferrithiocyanate method showed a correlation coefficient of 0.99, demonstrating the new method’s comparable effectiveness and reliability. In conclusion, a simple and reliable protocol for assessing CAT activity, which utilizes a cuvette or microplate, has been demonstrated in this study. This interference-free protocol can easily be used in research and clinical analysis with considerable accuracy and precision. Graphical Abstract Graphical Abstract